Dynamically crosslinked polymer nanocomposites to treat multidrug-resistant bacterial biofilms. Issue 39 (28th September 2018) - Zhu, Dong Yu; Landis, Ryan F.; Li, Cheng-Hsuan; Gupta, Akash; Wang, Li-Sheng; Geng, Yingying; Gopalakrishnan, Sanjana; Guo, Jian Wei; Rotello, Vincent M.
Abstract : Engineered phytochemical nanocomposites eliminate broad-spectrum biofilms in the presence of mammalian cells and degrade afterwards, reducing vehicle accumulation. Abstract : Multidrug-resistant biofilms are highly resistant to current antimicrobial therapies. We have developed an antimicrobial platform that integrates the bacteria-killing phytochemical carvacrol into dynamically crosslinked polymer nanocomposites (DCPNs). Taking advantage of a reversibly crosslinked Schiff-base scaffold throughout the engineered emulsions, DCPNs exhibited long-term shelf-life and good stability in serum, while readily disassembling in acidic microenvironments. Furthermore, we demonstrated that DCPNs efficiently penetrate the biofilm matrix, eradicating both Gram-negative/positive bacteria enclosed within. Moreover, DCPNs showed no observable toxicity to fibroblast mammalian cells with the same antimicrobial concentrations necessary to eradicate MDR biofilms. Given their potent antimicrobial and stimuli-responsive dissociation characteristics in a biofilm setting, DCPNs are a suitable therapeutic platform for combating MDR bacterial infections.